PRELIMINARY STUDY ON AGE, GROWTH AND REPRODUCTION OF MUSTELUS MUSTELUS (ELASMOBRANCHII: CARCHARHINIFORMES: TRIAKIDAE) INHABITING THE GULF OF ISKENDERUN, NORTH-EASTERN MEDITERRANEAN SEA - Ozcan, Ebru Ifakat; Basusta, Nuri (Wydawnictwo Akad Rolniczej W Szczecinie, 2018)
Background. Shark populations within the eastern Mediterranean are declining due to overfishing. Unfortunately, our knowledge on the biology of sharks and specifically dogfishes within eastern Mediterranean is extremely limited due to the lack of landings. Mustelus mustelus (Linnaeus, 1758) is one of such deficiently known cartilaginous fishes and the relevant information on its age and growth in the eastern Mediterranean is missing. The understanding of growth and reproductive behaviour is important for management and conservation of this species. The presently reported study was intended to determine age, growth, and some reproductive parameters of Mustelus mustelus collected in the Gulf of Iskenderun, the north-eastern Mediterranean Sea. Materials and methods. In this study, a total of 155 Mustelus mustelus were caught in the north-eastern Mediterranean Sea between March 2012 and October 2015. Fish age was determined based on band counts of sectioned vertebrae. The periodicity of band pair formation was examined using the marginal increment analysis. Growth parameters for all specimens were then determined by fitting the observed and the length-at-age data using the von Bertalanffy Growth Equation. The size and age at which 50% of both sexes reached maturity was estimated by a logistic model for maximum likelihood process and the gonadosomatic index was determined. Results. The total length and weight of the specimens examined ranged from 44.3 to 162.6 cm and from 241.3 to 12 060 g, respectively. The presently reported study provides new maximum lengths (162.6 cm) for M. mustelus from the north-eastern Mediterranean. The fish studied represented age groups from 0 through 25. The observed sex ratio was 1 divided by 1.04 (females divided by males). Von Bertalanffy growth parameters were estimated to be L-infinity = 195.13 cm, W-infinity = 20 060 g, K = 0.06, and t(0) = -4.27 for all specimens. Length-weight relation was found to be W = 0.0027L(3.0054) (R-2 = 0.98) and 95% confidence intervals of b = 2.936-3.075, t-test P < 0.05. All studied specimens of M. mustelus represented isometric growth (b = 3). Condition factor ranged from 0.148 to 2.87 for females and from 0.103 to 1.024 for males. The length at 50% maturity and the age at 50% maturity were 109 cm and 8 in females and 92 cm and 7 in males, respectively. It was observed that mean GSI values were low in September and July, reaching a maximum in January to February. Conclusion. The results of this study could give useful insight for management plans and conservation of M. mustelus in the Mediterranean coast of Turkey.
Keywords: smoothhound; Mustelus mustelus; length-weight relations; gonadosomatic index; condition factor